Expanding the Editing Window of Cytidine Base Editors With the Rad51 DNA-Binding Domain in Rice - Wei, Chunjie; Liu, Hao; Wang, Wenwen; Luo, Pengyu; Chen, Qiuling; Li, Rou; Wang, Chong; Botella, José Ramón; Zhang, Hui (Frontiers in Plant Science, 2022)
Recently developed base editors provide a powerful tool for plant research and crop improvement. Although a number of different deaminases and Cas proteins have been used to improve base editors the editing efficiency, and editing window are still not optimal. Fusion of a non-sequence-specific single-stranded DNA-binding domain (DBD) from the human Rad51 protein between Cas9 nickase and the deaminase has been reported to dramatically increase the editing efficiency and expand the editing window of base editors in the mammalian cell lines and mouse embryos. We report the use of this strategy in rice, by fusing a rice codon-optimized human Rad51 DBD to the cytidine base editors AncBE4max, AncBE4max-NG, and evoFERNY. Our results show that the addition of Rad51 DBD did not increase editing efficiency in the major editing window but the editing range was expanded in all the three systems. Replacing the human Rad51 DBD with the rice Rad51 DBD homolog also expanded the editing window effectively.